Repurposing of the Tamoxifen Metabolites to Combat Infections by Multidrug-Resistant Gram-Negative Bacilli - Andrea Miró-Canturri; Rafael Ayerbe-Algaba; Andrea Vila-Domínguez; Manuel E. Jiménez-Mejías; Jerónimo Pachón; Younes Smani (MDPI AG, 2021)
The development of new strategic antimicrobial therapeutic approaches, such as drug repurposing, has become an urgent need. Previously, we reported that tamoxifen presents therapeutic efficacy against multidrug-resistant (MDR) Acinetobacter baumannii, Pseudomonas aeruginosa, and Escherichia coli in experimental infection models by modulating innate immune system cell traffic. The main objective of this study was to analyze the activity of N-desmethyltamoxifen, 4-hydroxytamoxifen, and endoxifen, three major metabolites of tamoxifen, against these pathogens. We showed that immunosuppressed mice infected with A. baumannii, P. aeruginosa, or E. coli in peritoneal sepsis models and treated with tamoxifen at 80 mg/kg/d for three days still reduced the bacterial load in tissues and blood. Moreover, it increased mice survival to 66.7% (for A. baumannii and E. coli) and 16.7% (for P. aeruginosa) when compared with immunocompetent mice. Further, susceptibility and time-kill assays showed that N-desmethyltamoxifen, 4-hydroxytamoxifen, and endoxifen exhibited minimum inhibitory concentration of the 90% of the isolates (MIC90) values of 16 mg/L, and were bactericidal against clinical isolates of A. baumannii and E. coli. This antimicrobial activity of tamoxifen metabolites paralleled an increased membrane permeability of A. baumannii and E. coli without affecting their outer membrane proteins profiles. Together, these data showed that tamoxifen metabolites presented antibacterial activity against MDR A. baumannii and E. coli, and may be a potential alternative for the treatment of infections caused by these two pathogens.